Light yield non-proportionality of organic and inorganic scintillators exposed to alpha rays of various energy - Grinyov, B.V.; Tarasov, V.A.; Vydaj, Yu.T.; Kudin, A.M.; Andryushchenko, L.A.; Kilimchuk, I.V.; Ananenko, A.A.; Gordienko, L.S. (Functional Materials, 2006)
The influence of entrance surface for radiation state of Csl:TI, Csl:Na, stilbene and p-terphenyl scintillators on non-proportionality of light yield to the alpha-particle energy lias been studied. It has been shown that formation of disrupted near-surface layer results in increasing microheterogeneity of specific light yield over the crystal surface and depth. The organic and alkali-halide scintillator samples show considerable specific light output variations depending 011 alpha-particle energy. These samples have essential structural disruptions of entrance surface for radiation. A correlation is observed between the nonproportionality and pulse height resolution: the less non-proportionality is, the less is the pulse-height resolution value within the range of used alpha-particle energies. Исследовано влияние состояния входной для излучения поверхности сцинтилляторов Csl:TI, Csl:Na, стильбена и n-терфенила на непропорциональность светового выхода и энергии альфа-частиц. Показано, что образование приповерхностного нарушенного слоя приводит к увеличению микронеоднородностей удельного светового выхода по поверхности кристаллов и по глубине. Большими изменениями удельного светового выхода в зависимости от энергии альфа-частиц обладают образцы органических и щелочно-галоидных сцинтилляторов, имеющие существенные структурные нарушения входной для излучения поверхности. Между величиной непропорциональности и амплитудным разрешением наблюдается зависимость: чем меньше непропорциональность, тем меньше значение разрешения в диапазоне используемых энергий альфа-частиц. Проведено дослідження впливу стану вхідної для випромінювання поверхні сцинтиляторів Csl:TI, Csl:Na, стильбену і n-терфепілу на непропорційність світлового виходу і енергії альфа-часток. Показано, що утворення приповерхневого порушеного шару призводить до збільшення мікронеоднорідностей питомого світлового виходу вздовж поверхні кристалів і за глибиною. Великі зміни питомого світлового виходу, в залежності від енергії альфа-часток, характерні для зразків органічних і лужно-галоїдних сцинтиляторів, які мають істотні структурні порушення вхідної для випромінювання поверхні. Між величиною непропорційності і амплітудним розділенням спостерігається залежність: чим менше непропорційність, тим менше значення розділення у діапазоні енергій альфа-часток, що використовуються.